2011
DOI: 10.1002/mds.23872
|View full text |Cite
|
Sign up to set email alerts
|

Impact of apathy on health‐related quality of life in recently diagnosed Parkinson's disease: The ANIMO study

Abstract: The impact of apathy on health-related quality of life (HRQOL) in recently diagnosed Parkinson's disease (PD) has not been systematically investigated. The objective of this cross-sectional survey (ANIMO study) was to examine the contribution of apathy to HRQOL in a Spanish sample of recently diagnosed PD patients. PD patients, diagnosed within 2 years of inclusion, were recruited at 102 outpatient clinics in 82 communities throughout Spain. Apathy was quantified using the Lille Apathy Rating Scale and HRQOL w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
89
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 32 publications
13
89
2
1
Order By: Relevance
“…In the present study we also observed a trend for improvement in quality of life, which, in the absence of motor improvement, is likely related to the improvement of apathy, which is one of the key factors of reduced quality of life in patients with Parkinson's disease (Schrag et al, 2000;Chaudhuri and Schapira, 2009;Barone et al, 2010;Benito-Leon et al, 2012). However, in this relatively small series, this improvement did not reach significance level.…”
Section: Discussioncontrasting
confidence: 39%
“…In the present study we also observed a trend for improvement in quality of life, which, in the absence of motor improvement, is likely related to the improvement of apathy, which is one of the key factors of reduced quality of life in patients with Parkinson's disease (Schrag et al, 2000;Chaudhuri and Schapira, 2009;Barone et al, 2010;Benito-Leon et al, 2012). However, in this relatively small series, this improvement did not reach significance level.…”
Section: Discussioncontrasting
confidence: 39%
“…There were no treatment interventions during the course of this study. The ANIMO (Spanish word for 'good spirit') Group was formed in 2007 by a group of Spanish neurologists with expertise in PD [6] . We sampled a series of patients from 102 Spanish PD outpatient clinics from October 2008 to June 2009.…”
Section: General Study Designmentioning
confidence: 99%
“…In the present issue a review by Santangelo et al [16] specifically addressed apathy, i.e. lack of motivation, that is associated with decreased daily function, and increased stress for families [5,17]. Apathy has been traditionally considered as a symptom of psychiatric disorders, such as major depression and schizophrenia, but more recently it has been recognized as a specific neuropsychiatric syndrome associated with neurodegenerative diseases such as PD.…”
mentioning
confidence: 99%